2002
DOI: 10.1097/00001756-200201210-00024
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic genes expression in the lumbar dorsal horn in a model neuropathic pain in rat

Abstract: This study combines behavioural, molecular and morphological approaches to assess the occurrence of apoptosis in the rat spinal cord by 14-day sciatic nerve chronic constrictive injury (CCI). Thermal allodynia developed in the corresponding footpad 2-3 days after surgery, while morphological features, evaluated 14 days later, consisted in a decrease (23 +/- 7%) in laminae I-III cell number ipsilateral to CCI. Apoptosis occurrence was possibly suggested by the presence of some TUNEL-positive nuclei in this terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…The balance between Bax, a pro-apoptotic protein, and Bcl-2, an antiapoptotic protein, stabilizing membrane permeability is very important in apoptosis induction (Oltvai et al 1993). Our western blot data showed that Bax/Bcl-2 ratio was elevated following CCI, supporting evidence that in the CCI of sciatic nerve, the development of neuropathic pain may be associated with the activation of apoptosis (Siniscalco et al 2007, Maione et al 2002. Bax/Bcl2 ratio declined in the spinal cord of rats treated with saffron's extracts on day 3.…”
Section: The Effects Of Crocus Sativus Extracts On the Bax And Bcl2 Psupporting
confidence: 82%
See 1 more Smart Citation
“…The balance between Bax, a pro-apoptotic protein, and Bcl-2, an antiapoptotic protein, stabilizing membrane permeability is very important in apoptosis induction (Oltvai et al 1993). Our western blot data showed that Bax/Bcl-2 ratio was elevated following CCI, supporting evidence that in the CCI of sciatic nerve, the development of neuropathic pain may be associated with the activation of apoptosis (Siniscalco et al 2007, Maione et al 2002. Bax/Bcl2 ratio declined in the spinal cord of rats treated with saffron's extracts on day 3.…”
Section: The Effects Of Crocus Sativus Extracts On the Bax And Bcl2 Psupporting
confidence: 82%
“…Scientific studies have verified many traditional uses of such expensive spice. Saffron Pain initiated or caused by a primary lesion or dysfunction in the nervous system is defined as being a neuropathic pain and triggers a cascade of events in the central or peripheral nervous system, including excitotoxicity, oxidative stress, inflammatory process and apoptotic like cell death mechanisms (Maione et al 2002). In our previous work, antiallodynic and antihyperalgesic effects of ethanolic and aqueous extracts of saffron were shown in rats that underwent chronic constriction injury (CCI) of the sciatic nerve .…”
Section: Introductionmentioning
confidence: 99%
“…The measured mRNA levels were normalized with three housekeeping genes: hypoxanthine-guanine phosphoribosyltransferase (HPRT), 18S ribosomal RNA (18S), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH). The HPRT, 18S, and GAPDH housekeeping genes were chosen because their gene expression did not change in different experimental conditions including SNI-induced neuropathic pain (Bangaru et al 2012;Maione et al 2002;Piller et al 2013;Siniscalco et al 2007Siniscalco et al , 2010. The gene expression values are expressed as arbitrary units Ϯ SE.…”
Section: Methodsmentioning
confidence: 99%
“…de Novellis et al (2004) reported an apparent reduction of ϳ50% in the number of neurons in lamina II on both sides of the spinal cord 7 d after CCI. However, these authors previously detected a reduction of only 23% of neurons in laminas I-III on the ipsilateral side 14 d after CCI (Maione et al, 2002). It is hard to reconcile these two findings, and because they were both obtained from simple profile counts, rather than with a stereological method (see below), they must be treated with considerable caution.…”
Section: Numbers Of Neurons In Laminas I-iiimentioning
confidence: 99%